The Curious Case of Earth’s Survival v. The World’s Development - Wilson, Natasha Christina Davis (UI Scholars Hub, 2011)
The over exploitation of marine life is the first part of the planetary crisis. The second part of the crisis arises because man is ambitious and cannot be stopped from progressing everyday. This creates a dominoes effect, by raising concerns about species dependent on marine life, which would be everybody else. This threat on marine life along with hitherto unprecedented levels of development on a very fragile earth can lead to a very bleak future. Development and progress have made the world a smaller place. Development and progress have also ensured that there isn't so much of the earth left to go around. The nations of the world have always agreed that developing sustain ably and with precaution is the only way forward if we are to have a future. We come to a juncture where what is legally sound may not be morally acceptable. Here arises the problem of balancing. This paper considers the earth’s journey from the Stockholm Conference of 1972 and The Rio Declaration of 1992 to marine life and international trade issues faced by us today. It draws conclusions by tracing the evolution and the competition between the two parts of the planetary crisis. The paper offers an alternative story of the future, if the balance is not maintained between international norms and development by the nations of the world, by bringing forth paradigm shifts in the planetary crisis between ambitious nations and the survival of the living earth.